Experimental study of the pharmacokinetics of monoclonal antibodies to α4β1-integrin in guinea pigs - B. N. Krapivin; O. V. Goncharova; E. L. Morozova (Биопрепараты: Профилактика, диагностика, лечение)
This article presents the data on pharmacodynamics evaluation of monoclonal antibodies to α4β1-integrin in guinea pigs. The effect on total content of peripheral blood leukocytes after a single intraperitoneal injection of three doses of the drug has been studied. It was shown that intraperitoneal injection of the drug at doses of 30, 60, and 120 mg/kg causes a twofold increase in the content of leukocytes in the first hours after the administration, reaching a maximum value to 6th day. Subsequently 11-18 days, depending on dose, leukocytes content gradually decreased to control values.